Career Nomadism as a New Social Identity: A Phenomenological Study of Generation Z in Denpasar and Badung - I Komang Bagus Krisna Bhaskara; Putu Irma Yunita (International Journal of Science and Society, 2026)
This study examines how career nomadism is interpreted and experienced by Generation Z workers in Denpasar and Badung, Bali, with particular attention to its role in shaping identity within non-linear career trajectories. Employing a qualitative design, this research adopts Interpretative Phenomenological Analysis (IPA) to explore participant’s lived experiences and subjective meaning-making. Data were collected through in-depth, semi-structured interviews with ten Generation Z workers who had undergone repeated cross-role or cross-sector career transitions. The findings reveal three interrelated themes: autonomy-seeking as career agency, uncertainty negotiation through competence formation, and relational validation in identity construction. Career mobility is not perceived as instability but as a reflective and adaptive strategy through which individuals maintain agency, develop competencies, and align work with personal values. Autonomy emerges as the primary motivational anchor, while competence and relatedness function as enabling and stabilizing forces that sustain professional legitimacy. Within the socio-cultural context of Denpasar and Badung, career nomadism is continuously negotiated against norms privileging stable employment, positioning it as an emerging form of social identity. By integrating Identity Work Theory and Self-Determination Theory, this study offers a nuanced understanding of how motivational and relational dynamics sustain non-linear career pathways.